1991
DOI: 10.1099/00221287-137-5-1213
|View full text |Cite
|
Sign up to set email alerts
|

One-step purification of cholesterol oxidase from culture broth of a Pseudomonas sp. using a novel affinity chromatography method

Abstract: Cholesterol oxidase from the culture broth of a Pseudomonas sp. was purified with a yield of more than 70% by a one-step procedure using a column of cholesterylglycine-carboxymethylcellulose; active enzyme was eluted by Triton X-100. The purified enzyme was homogeneous by SDS-PAGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…However, in this study, we found that the recombinant ChoM1 and ChoM2 enzyme activities were strongly stimulated by Mg 2+ and Mn 2+ . The Mn 2+ stimulation effect on ChoM1 and ChoM2 was in accordance with cholesterol oxidase from Pseudomonas sp . Besides, the observed K m and V max values of the recombinant enzymes towards cholesterol and other substrates (data not shown) indicate that both ChoM1 and ChoM2 show higher activity towards the 3β‐hydroxy steroids with long alkyl chains at C17.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, in this study, we found that the recombinant ChoM1 and ChoM2 enzyme activities were strongly stimulated by Mg 2+ and Mn 2+ . The Mn 2+ stimulation effect on ChoM1 and ChoM2 was in accordance with cholesterol oxidase from Pseudomonas sp . Besides, the observed K m and V max values of the recombinant enzymes towards cholesterol and other substrates (data not shown) indicate that both ChoM1 and ChoM2 show higher activity towards the 3β‐hydroxy steroids with long alkyl chains at C17.…”
Section: Discussionsupporting
confidence: 59%
“…The Mn 2+ stimulation effect on ChoM1 and ChoM2 was in accordance with cholesterol oxidase from Pseudomonas sp. 43 Besides, the observed K m and V max values of the recombinant enzymes towards cholesterol and other substrates (data not shown) indicate that both ChoM1 and ChoM2 show higher activity towards the 3 -hydroxy steroids with long alkyl chains at C17. The enzyme property studies provide a reliable theoretical basis for the culture medium optimization and the fermentation process improvement in order to improve the bioconversion efficiency.…”
Section: Discussionmentioning
confidence: 88%
“…Rhee et al purified an active enzyme from the culture supernatant of a Pseudomonas sp. with a yield of 70% by using cholesterylglycine-CM-cellulose column [76]. The CHOx enzyme produced by Enterococcus hirae was precipitated at 80% ammonium sulphate saturation and then purified by applying on Sephadex G-100 gel chromatography column with resultant yield of 79% and 2.3-fold purification.…”
Section: Characterization Of Cholesterol Oxidasementioning
confidence: 99%
“…Lately, Rhee et al (1991) described the synthesis of a novel cholesterol affinity adsorbent and a very simple purification procedure that gives a high yield of homogeneous cholesterol oxidase from culture broth of a Pseudomonas sp.…”
Section: Purification Of Cholesterol Oxidasementioning
confidence: 99%